A forest charm - Bentley, Sue, 1951-; Farley, Andrew; Swan, Angela (New York : Grosset & Dunlap, 2010)
Cassie is nervous when she must accompany her parents on a team-building vacation in the woods with people she does not know, but her anxiety is eased when Storm, the magic puppy, shows up.
edited hb 2015-06-16
Keywords: Camping -- Fiction; Dogs -- Fiction; Magic -- Fiction